Strategy: Winning in the Marketplace: Core Concepts, Analytical Tools, Cases - A. Thompson Arthur (McGraw -Hill, 2006)
STRATEGY: Winning in the Marketplace is the newest offering from proven authors Thompson, Gamble, and Strickland. As in previous works, the authors' mainstream presentation includes the most recent research in strategy presented in a way that students can understand and apply to business cases and problems. With fewer chapters and pages and shorter cases than previous texts by these authors, this new first edition offers a more concise, lively, and user-friendly presentation of strategic management. Fundamental strengths of Thompson/Gamble/Strickland text treatments are very much evident in this first edition-a compelling presentation of Porter's Five-Forces model and globally competitive markets and first-rate coverage of strategy execution and the drive for operating excellence. Another hallmark of this new product is the package of Thompson/Gamble/Strickland cases and related teaching notes. Over the years, this author team has developed a great network of case authors and is able to select from the cream of the crop. Having written scores of cases themselves and having a combined experience of 70 years teaching this particular course, they are very skilled in selecting the types of cases that will spark student interest and generate lively classroom discussions. Many of the cases reflect high profile industries, companies, products, and people that students will have heard of, know about from personal experience, or can easily identify with. The new case line-up features an exciting collection of the latest and best cases flush with valuable teaching points and lessons for students. -